POWER GENERATION FROM PRESSURE REDUCTION IN THE NATURAL - Rahman, Mohammed Mahbubur (Journal of Mechanical Engineering, 2011)
Power can be generated from the pressure energy of natural gas along its supply chain at various pressure reduction points by using turbo-expanders. This technology is being applied in different countries around the world. This paper attempts to asses the potential of using this technology for Bangladesh. A number of producing wells and pressure reduction stations are investigated. It is found that pre-heating before expansion is almost always necessary to avoid hydrate formation. The power obtainable at the wellheads range from 150-500 kW, and that from pressure reduction stations range from 200 kW to 5 MW. DOI: http://dx.doi.org/10.3329/jme.v41i2.7472